Pengaruh Kualitas Pelayanan, Kualitas Produk, Dan Harga Terhadap Minat Beli Pada Klinik Kecantikan Khayla Beauty - Rahmawati, Novia; Sukaris (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2024)
The study aims to find out the influence of the variables of service quality, product quality, and price on purchasing interest in khayla beauty clinics. The study uses a quantitative approach involving 100 patients from the clinic concerned. The analytical techniques used are double linear analysis with the help of SPSS version 26, while the data sources are derived from primary and secondary data. Data collection is carried out through the dissemination of questionnaires to respondents. The results of the analysis showed that the variables of service quality, product quality, and price influenced purchasing interest at Khayla Beauty. The analysis of the double linear regression coefficient indicated that the highest value was obtained from the product quality variable. In other words, the higher the quality of the given product, the greater the purchasing interest that appears in the consumer. This study has its limitations because it was only done on the consumers of the Khayla Beauty Clinic.